2015
DOI: 10.1128/aac.00714-15
|View full text |Cite
|
Sign up to set email alerts
|

The Efflux Pump SmeDEF Contributes to Trimethoprim-Sulfamethoxazole Resistance in Stenotrophomonas maltophilia

Abstract: Trimethoprim-sulfamethoxazole (co-trimoxazole) is one of the antimicrobials of choice for the treatment of Stenotrophomonas maltophilia infections. The analysis of mutants either lacking or overexpressing the efflux pump SmeDEF shows that this efflux pump contributes to intrinsic and acquired co-trimoxazole resistance in S. maltophilia. Since SmeDEF can extrude a variety of antibiotics, selection with such antimicrobials, including quinolones, might also select for S. maltophilia co-trimoxazole resistance.T he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 19 publications
(21 reference statements)
1
26
1
Order By: Relevance
“…SmeVWX is not involved in the intrinsic co-trimoxazole resistance of S. maltophilia. We have previously described that SmeDEF contributes to intrinsic and acquired co-trimoxazole resistance in S. maltophilia (18). The results presented in the current work indicate that SmeVWX, when overexpressed, is a relevant element in the acquisition of S. maltophilia co-trimoxazole resistance as well.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…SmeVWX is not involved in the intrinsic co-trimoxazole resistance of S. maltophilia. We have previously described that SmeDEF contributes to intrinsic and acquired co-trimoxazole resistance in S. maltophilia (18). The results presented in the current work indicate that SmeVWX, when overexpressed, is a relevant element in the acquisition of S. maltophilia co-trimoxazole resistance as well.…”
Section: Resultssupporting
confidence: 69%
“…Indeed, different studies have shown that the activity of some efflux pumps might affect S. maltophilia co-trimoxazole susceptibility. Among these studies, it has been shown that the overexpression of SmeDEF reduces the susceptibility to co-trimoxazole of S. maltophilia, while the inactivation of this efflux pump increases the bacterial susceptibility to this antimicrobial (18). Other studies have shown that the deletion of the efflux pump SmeYZ or of the outer membrane protein TolC, the latter required for the activity of the efflux pump SmeOP, increases the susceptibility of S. maltophilia to co-trimoxazole (19)(20)(21).…”
mentioning
confidence: 99%
“…Community-acquired S. maltophilia infections, especially in the high-risk populations mentioned, have been reported (5), and recently, a communityacquired skin infection was reported for the first time in an immunocompetent individual (6). The multidrug-resistant nature of S. maltophilia makes treatment of infections highly difficult (7), and in recent years, an increased resistance to the preferred antibiotic trimethoprim-sulfamethoxazole has been reported (8)(9)(10). These findings emphasize the need to better understand the virulence mechanisms employed by S. maltophilia.…”
mentioning
confidence: 88%
“…The present results demonstrated that S. maltophilia was resistant to AMO, OXA and SPE, even without being exposed to CA (Table 2). S. maltophilia is commonly described as an opportunistic pathogen with intrinsic multidrug-resistance (Zhang et al, 2000;S anchez, 2015;Adegoke et al, 2017;Rizek et al, 2018). However, it is also known that S. maltophilia can acquire resistance (Song et al, 2010;Furlan et al, 2018;Rizek et al, 2018).…”
Section: Conditionmentioning
confidence: 99%
“…It is important to emphasize that the concentrations used in that study are the therapeutic doses (CA e 28.6 mg/kg/d, EA e 2.9 mg/kg/d and 2,4-D e 70 mg/kg/d) which are significantly higher than the trace concentrations detected in environment (170e17000 ng/L). TMP-SMX is the most common therapeutic option used to treat S. maltophilia infections (Emblidge and DeLorenzo, 2006;S anchez and Martínez, 2015) and tolerance to this combination of antibiotics was not observed despite the exposure of S. maltophilia to CA.…”
Section: Conditionmentioning
confidence: 99%